The image of the beautiful woman - Lotti, Valeria (Enthalten in:Asien;Hamburg : DGA, 1981;(2018), 147, Seite 92-104, 2018)
lmages of the female body are widely employed in advertising, cinema, fashion, and media the world over. In Chinese cities, meanwhile, everywhere we look we can see advertisement for cosmetic treatments that depict desirable bodily representations with the following core characteristics: thin figure, oval face with pointed chin, slim cheeks, high-bridged nose, big eyes, and fair skin. These are the supposed features of the modern beautiful woman, and set the beauty standards that cosmetic treatments aim to reach up to. The beauty standards promoted nowadays are, to a certain extent, the result of globalization and individualization: with the reform era the diffusion of Western (i.e. Euro-American) culture in China had an impact on existent norms of beauty, creating new global and local standards - ones that women choose to pursue as a way to affirm their individual identity. This Research Note focuses on the ideals of beauty that are currently widespread in Chinese society, highlighting specifically the cultural and social influences that have shaped them. Additionally it points out the currently popular cosmetic surgery trends, as they embody perfectly such ideals of beauty - and thus ultimately attempts to show the power of body images in the construction of modern individuals. (Asien/GIGA)
Beauty in East Asia
Keywords: Popkultur; Frau; Ästhetik; Chirurgie; Sozialverhalten; Soziales Feld; Einflussgröße; Kultur; Globalisierung; Individualismus